If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.62 + -0.15x = 0.25 + -0.1 Combine like terms: 0.25 + -0.1 = 0.15 0.62 + -0.15x = 0.15 Solving 0.62 + -0.15x = 0.15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.62' to each side of the equation. 0.62 + -0.62 + -0.15x = 0.15 + -0.62 Combine like terms: 0.62 + -0.62 = 0.00 0.00 + -0.15x = 0.15 + -0.62 -0.15x = 0.15 + -0.62 Combine like terms: 0.15 + -0.62 = -0.47 -0.15x = -0.47 Divide each side by '-0.15'. x = 3.133333333 Simplifying x = 3.133333333
| f(x)=2x-3x+4 | | -7x+3=-11 | | -15-5t=15 | | 5x-4(-3/2x+2)=y | | 5x-5=12-68 | | f(x)=2x(4)-3x+4 | | 4x+13=8x+25 | | -x+42=4x | | -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 |